The Reasons for Foreign Exchange Reserves Accumulation in Hong Kong: A Cointegration and Vector Error Correction Approach - Jiang, Cheng (Asian Economic and Financial Review, 2018)
This paper empirically investigates the reasons for the large amounts of foreign exchange reserves accumulation in Hong Kong in both long run and short run. The Johansen cointegration test results show a positive long-run relationship between broad money supply and foreign exchange reserves holding, and no significant long-run relationship between exchange rate and foreign exchanges reserve holding, indicating that the increase in money supply is a reason for the rise of foreign exchange reserves holding in long run. The long-run relationships are confirmed by Granger causality test results, and are explained by Hong Kong’s small open economy under fixed exchange rate regime. This paper establishes a vector error correction model to measure the short-run dynamics and the tendency to restore to its long-run equilibrium. The coefficient of error correction term implies a low speed of adjustment of foreign exchange reserves, indicating that the monetary authority of Hong Kong has to hold large amounts of foreign exchange reserves to be effective in foreign exchange reserves intervention and management. The low speed of adjustment in the short run is the second reason why Hong Kong’s foreign exchange reserves holding increases rapidly.